Antibiotic Resistance Profile of Enterovirulent E. coli Isolates Harboring Broad-Spectrum Beta-Lactamase Genes in Cancer Patients at the Laquintinie Hospital in Douala, Littoral Region, Cameroon - Michael F. Kengne; Armelle T. Mbaveng; Wiliane J. T. Marbou; Ousenu Karimo; Ballue S. T. Dadjo; Delano G. T. Fonjou; Ornella D. Tsobeng; Victor Kuete (International Journal of Microbiology)
Cases of antibiotic-resistant Escherichia coli (E. coli) infections are becoming increasingly frequent and represent a major threat to our ability to treat cancer patients. The emergence of antimicrobial resistance threatens the treatment of E. coli infections. In this study, the antimicrobial profiles, virulent genes, and the frequency of extended-spectrum beta-lactamase (ESBL) gene carriage in fecal E. coli isolates from cancer patients at the Laquintinie Hospital in Douala (Cameroon) were determined. 507 participants were recruited from October 2021 to March 2023, of whom 307 (60.55%) had cancer and 200 (39.45%) did not. Two hundred and two E. coli were isolated from fecal samples of one hundred and fifteen cancer patients and 47 (87) noncancer patients using EMB LEVINE agar. The antimicrobial resistance profile of the isolates was determined using the Kirby–Bauer disk diffusion method. Virulence and resistance genes were detected by simplex polymerase chain reaction (PCR). E. coli showed significant rates of resistance to amoxicillin, cefotaxime, ceftazidime, piperacillin, tetracycline, and ciprofloxacin in cancer patients compared to noncancer patients. The rate of multidrug resistance (MDR) was significantly (p<0.05) higher in cancer patients than in noncancer patients. Fifty-five enterovirulent E. coli were identified, of which 24 (43.63%) were EPEC, 13 (23.63%) were EAEC, 6 (10.90%) were ETEC, 10 (18.18%) were STEC, and 2 (3.63%) were EIEC. The frequency of beta-lactamase genes in the 55 ESBL-producing enterovirulent E. coli isolates was determined, and 94.54% harbored at least one ESBL gene, distributed as follows: 80.00% for blaTEM, 67.27% for blaCTX−M, 24.63 for blaOXA, and 36.36% for blaSHV genes. Several associations were observed between virulence factors, resistance genes, and the antimicrobial resistance phenotype. This study revealed the real existence of fecal carriage of ESBL-producing enterovirulent E. coli isolates from cancer patients with a high rate of MDR in the latter.